Criminology MA (Academic Journal of Internal Affairs, 2021)
The Criminology MA book has primarily been written for Master’s students at the Faculty of Law Enforcement of the University of Public Service as it covers some of the most current and important international and Hungarian research within the field of criminology. Its topics include, among other things, crime prevention strategies, crime prevention through environmental design, child-friendly justice practices and the consequences of drug use. The main question of the volume of studies edited by Andrea Tünde Barabás is which criminological topics can provide the students with the newest and hopefully the most useful knowledge. The volume consists of three chapters: Theory and practice of crime prevention; Criminology of children and the elderly; and Drug-related crimes and drug use.
Keywords: recension; criminology; crime prevention